Investigating constraint-based reasoning for University timetabling problem - Ho, Sheau Fen@Irene, author; Safa'ai Deris, 1955-, author; Siti Zaiton Mohd. Hashim, author; International MultiConference of Engineering and Computer Science (2009 : Hong Kong) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL